Reshaped as polyester-based nanoparticles, gallic acid inhibits platelet aggregation, reactive oxygen species production and multi-resistant Gram-positive bacteria with an efficiency never obtained. Issue 10 (27th September 2019) - Alfei, Silvana; Signorello, Maria Grazia; Schito, Anna; Catena, Silvia; Turrini, Federica
Abstract : A gallic acid nanoformulation acts as a strong platelet aggregation, ROS and bacterial growth inhibitor. Abstract : Natural polyphenols such as Gallic Acid (GA) form an important class of bioactive chemical entities that, having innumerable biological properties, could represent a safer alternative to common drugs against several disorders, including platelet aggregation, radical oxygen species (ROS) hyperproduction, oxidative stress (OS) and bacterial infections. Unfortunately, their clinical uses are limited by pharmacokinetics drawbacks and high sensitivity to environmental factors. In order to overcome these problems and to exploit the GA curative potentials, it has been linked to a biodegradable nanospherical dendrimer matrix, capable of protecting it, thus obtaining a GA-enriched nanosized dendrimer (GAD) endowed with a strong antioxidant capacity. GAD activity as an inhibitor of platelet aggregation and ROS accumulation and its antibacterial efficiency are evaluated here and compared to those of free GA, obtaining outcomes never achieved. Regarding platelet aggregation induced by thrombin and collagen, the GAD proved to be stronger by 7.1 and 7.3 times, respectively. Furthermore, the GAD showed a ROS inhibitory activity higher than that of GA by 8.1 (thrombin) and 6.9 (collagen) times. Concerning the antibacterial activities, evaluated on eleven multi-resistant Gram-positive strains of clinical relevance, the GAD is far more potent than GA, by exerting a growth inhibitory activity at MIC (μM) concentrations lower by factors in the range 12–50.